Regeneration in Echinoderms: Molecular Advancements - Medina-Feliciano, Joshua G.; García-Arrarás, José E. (Frontiers in Cell and Developmental Biology, 2021)
Which genes and gene signaling pathways mediate regenerative processes? In recent years, multiple studies, using a variety of animal models, have aimed to answer this question. Some answers have been obtained from transcriptomic and genomic studies where possible gene and gene pathway candidates thought to be involved in tissue and organ regeneration have been identified. Several of these studies have been done in echinoderms, an animal group at the base of the vertebrate evolutionary branch. Echinoderms, with their outstanding regenerative abilities, can provide important insights into the molecular basis of regeneration. Here we review the available data, to determine the genes and signaling pathways that have been proposed to be involved in regenerative processes. Our analyses provide a curated list of genes and gene signaling pathways and match them with the different cellular processes of the regenerative response. In this way, the molecular basis of echinoderm regenerative potential is revealed, and are available for comparisons with other animal taxa.